Optimum Volume of Freeway Corridors. Issue 3 (March 2020) - Shojaat, Siavash; Geistefeldt, Justin; Wolshon, Brian
Conventional methods to assess the quality of service on freeways are based on the comparison of a specific peak hour traffic demand to the capacity of the facility, which is usually measured at a single uniform bottleneck section. However, estimating the quality of service of one bottleneck section may not be sufficient to assess the performance of an entire freeway facility. A driver traveling along a freeway corridor may actually encounter multiple flow breakdowns at independent bottleneck sections, which affect the overall quality of service. This paper introduces a comprehensive approach that considers an entire freeway corridor as a system consisting of successive independent bottlenecks with different characteristics, and can be used to estimate the optimum sustainable volume. The methodology is based on the sustained flow index, which is defined as the product of traffic volume and the probability of survival at this volume. Optimum volumes of two real-world corridors are estimated based on the new derivations. The empirical results reveal that the optimum volume and the capacity of an entire corridor is less than those of its most restrictive bottleneck.